PERAN BANK SUMUT CABANG SYARIAH DALAM MENINGKATKAN USAHA MIKRO KECIL DAN MENENGAH DI KOTA PEKANBARU - Mutiara, Rindi; Ratna, Ratna (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The role of Bank Sumut Sharia Branch in Dumai in promoting businesses for MSMEs has become a significant concern. Data obtained indicate that financing for MSMEs is still relatively low, and the number of MSME customers has not reached the expected expectations. Additionally, the development of MSMEs in Dumai has also shown a decline in the last five years. Therefore, this study aims to analyze the role of Bank Sumut Sharia Branch in enhancing MSMEs in Padangidimpuan. The method used is a qualitative descriptive method, with data sources derived from primary and secondary data. Data collection for this study uses field observation techniques, interviews with employees of Bank Sumut Sharia Branch Dumai, specifically in the Financing Department (AO), as well as customers, and documentation. For data analysis techniques, this study uses three methods: data reduction, data presentation, and then drawing conclusions. The results show that the role of Bank Sumut Sharia Branch in Dumai covers several important aspects. First, the Bank has provided business capital loans to MSMEs to increase their capacity in developing their businesses. Second, through this financing, the income of MSMEs that have received support from the Bank has also experienced significant increases. Furthermore, Bank Sumut Sharia Branch plays a crucial role in enabling the circulation of capital among similar MSMEs that have developed, thus creating broader success in the MSME sector and making a positive contribution to local economic growth.